Political spectacle and the fate of American schools - Smith, Mary Lee (Critical social thought., 2004)
The authors argue that the most influential and well-known educational policy programs in the past 30 years are not based on democratic consensus, but are instead formulated by the political community as symbolic efforts meant to generate personal.